Preprocessing Techniques in SCVRP Model: Case of Rubbish Transportation Problem in Kecamatan Ilir Barat II Palembang South Sumatera Indonesia - Irmeilyana Irmeilyana; Fitri Maya Puspita; Indrawati Indrawati; Ferani Eva Zulvia (Institute of Advanced Engineering and Science, 2012)
Rubbish transportation activities in Palembang can be considered as one of the application of Vehicle Routing Problem (VRP). We call it Symmetric Capacitated Vehicle Routing Problem (SCVRP) since we allow two way direction routes. We focus on rubbish transportation of Kecamatan Ilir Barat II Palembang, one of the biggest districts in Palembang to be simplified using preprocessing techniques to achieve simpler SVCRP model. This technique can simplify the model through some stages such as strengthening the bounds of constraint, eliminating redundant variables or fixing the variables [1]. The results show that preprocessing techniques can create simpler SCVRP formulation and easily solve the problem with aid of optimization tool.